2011
DOI: 10.1186/1758-5996-3-31
|View full text |Cite
|
Sign up to set email alerts
|

L-carnitine ameliorated fatty liver in high-calorie diet/STZ-induced type 2 diabetic mice by improving mitochondrial function

Abstract: BackgroundThere are an increasing number of patients suffering from fatty liver caused by type 2 diabetes. We intended to study the preventive and therapeutic effect of L-carnitine (LC) on nonalcoholic fatty liver disease (NAFLD) in streptozotocin (STZ)-induced type 2 diabetic mice and to explore its possible mechanism.MethodsThirty male Kungming mice were randomly divided into five groups: control group, diabetic group, pre-treatment group (125 mg/kg BW), low-dose (125 mg/kg BW) therapeutic group and high-dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
41
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 38 publications
5
41
0
Order By: Relevance
“…We added a mixture of 10 mM L-carnitine (Sigmatau Inc., Gaithersburg, MD) and 50 nM exendin-4 (Sigma Aldrich, St. Louis, MO) to the perfusate upon commencement of NELP. The chosen doses were based on previous reports (21)(22)(23)(24)(25) with effective protocols for reducing hepatocyte IRI and steatosis. Cholesterol, triglyceride (TG), and low-density lipoprotein (LDL) levels were then measured in the blood perfusate.…”
Section: Defatting Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…We added a mixture of 10 mM L-carnitine (Sigmatau Inc., Gaithersburg, MD) and 50 nM exendin-4 (Sigma Aldrich, St. Louis, MO) to the perfusate upon commencement of NELP. The chosen doses were based on previous reports (21)(22)(23)(24)(25) with effective protocols for reducing hepatocyte IRI and steatosis. Cholesterol, triglyceride (TG), and low-density lipoprotein (LDL) levels were then measured in the blood perfusate.…”
Section: Defatting Protocolmentioning
confidence: 99%
“…We selected L-carnitine (21) and exendin-4 (22)(23)(24) to increase the rate of fatty acid metabolism within the cytoplasm and mitochondria of hepatocytes. L-carnitine increases the rate of fatty acid transport to the mitochondria and, in fact, has been shown to be essential to b-oxidation of quarried fatty acids from the mitochondrial membrane.…”
Section: Reduction Of Iri and Steatosis With Nelpmentioning
confidence: 99%
“…Recent studies have shown that L -carnitine plays an important role in reducing steatosis in patients with hepatitis C treated with IFN-α and ribavirin [33]. L -Carnitine supplements greatly improved glucose plasma levels, lipid profiles, and histological manifestations in patients with nonalcoholic steatohepatitis [34]. Therefore, β-HPC appears to retain the pharmacological effects of L -carnitine and treat disturbances in the hepatic lipid metabolism of obese rats.…”
Section: Discussionmentioning
confidence: 99%
“…L-carnitine supplementation reduces the chance of long-chain acylcarnitine accumulation in mitochondria space and therefore, protects membrane against destruction. Diabetes is along with oxidative stress which affects antioxidative defense against RoS [11,21]. Therefore, mitochondria protective effects of L-carnitine can be considered as Lcarnitine beneficial effects observed in STZ-induced diabetic rats.…”
Section: T a B L E 2 Body Weight Glucose Insulin And Adiponectin mentioning
confidence: 99%
“…Also, it has been reported that high dose of L-carnitine reduced diabetes severity and also improved cardiac function [10]. Xia Y. et al showed that oral administration of L-carnitine to mice was increased β-oxidation of fatty acids and also in liver maintained mitochondrial function [11].…”
mentioning
confidence: 99%